2018
DOI: 10.1080/00365521.2018.1438508
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection of non-ampullary sporadic duodenal adenomas: a retrospective analysis with long-term follow-up

Abstract: EMR for NASDA is effective with a favorable long-term outcome. Local recurrences can be retreated endoscopically. A recall system, patient's compliance to endoscopic follow-up are mandatory to detect recurrences and their prompt treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…However, previous studies showed that incomplete resection including piecemeal resection was not associated with long-term recurrence in SNDA Indeed, one-third of patients underwent piecemeal EMR in the present study; however, no recurrence was observed during follow-up. In a study reporting 75 SNDA treated with EMR, residual and recurrence rate was 14.5 and 10.9%, respectively, during median 59 months of follow-up period [27]. However, all but one was successfully treated endoscopically that showed favorable long term outcome.…”
Section: Discussionmentioning
confidence: 98%
“…However, previous studies showed that incomplete resection including piecemeal resection was not associated with long-term recurrence in SNDA Indeed, one-third of patients underwent piecemeal EMR in the present study; however, no recurrence was observed during follow-up. In a study reporting 75 SNDA treated with EMR, residual and recurrence rate was 14.5 and 10.9%, respectively, during median 59 months of follow-up period [27]. However, all but one was successfully treated endoscopically that showed favorable long term outcome.…”
Section: Discussionmentioning
confidence: 98%
“…The final diagnosis of NADLs after ER could be different from the pre-ER forceps biopsy results. [ 24 ] Therefore, though no adenoma is observed in the pre-ER biopsy, once endoscopic findings show an adenomatous polyp, it is necessary to perform ER. Indeed, previous studies have indicated that some endoscopists think pre-resection biopsy was not important and prefer not to perform forceps biopsy before ER in NADL since forceps biopsy can cause fibrosis around the lesion and the result after ER can be higher by up to 40%; a pre-ER biopsy is unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that AEs occurred only during the ESD procedure. Recently, several studies have shown the clinical outcomes of ER of NADETs 19 20 21 27 . These reports showed that EMR is more suitable and safer than ESD, especially for small lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Those reports have shown that NADETs of the gastric phenotype have a higher malignant potential than those of the intestinal type. Recently, several groups of investigators reported on long-term outcomes of ER of NADETs 19 20 21 22 . However, the association between clinical outcomes of ER and mucin phenotypes has not been elucidated in detail.…”
Section: Introductionmentioning
confidence: 99%